(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
This article is a continuation of the publication of the rare species of bryophytes in Ukraine. The characteristic of rare species of Bryophyta division (Sphagnopsida and Bryopsida class) is given. These species are included to The Red Data Book of European Bryophytes, The Annex of The Berne Convention, The Red Data Book of Ukraine, The Red List of Bryophytes of Ukraine and Checklist of European Bryophytes on the establishment of European Red List. 5 species are rare for Sphagnopsida class, 96 species – for class Bryopsid. The greatest number of rare species is presented in Pottiaceae family – 21, Amblystegiaceae – 7, Fissidentaceae, Funariaceae, Orthotrichaceae – 6 species; in genera Fissidens – 6, Sphagnum – 5, Tortula – 4 species. Described species need to be considered critically in order to define measures of their protection in Ukraine.